Use of three-dimensional versus mini fixation plates in open reduction of mandible fractures in patients of a Mexican hospital between 2017-2023 - Cerón-Solano, Giovanni; Hernández-Ordoñez, Ruben; Covarrubias-Noriega, Alejandro; Rojas-Ortiz, Jorge; Vázquez-Morales, Lya; Pacheco-López , Ricardo (International Journal of Research in Medical Sciences, 2023)
Background: Mandibular fractures are the second most frequent facial fracture, after nose fractures. There are multiple treatments, with reduction and fixation with osteosynthesis plates being the gold standard. Our surgical center uses two types of osteosynthesis plates, 3D, and linear plates. We designed a study to assess whether the use of a 3D plate results in an improvement in terms of surgical time, bleeding volume and post-surgical complications. Methods: We measured bleeding and surgical time from the incision to its closure. Evaluation of the results by computerized axial tomography was obtained at 3 months post-surgery, as well as clinical evaluation of occlusion and other complications. Results: Sixty-three patients met the inclusion criteria. Overall, a 7.9% rate of complications was observed; 5.7% for patients treated with 3D osteosynthesis plates and 10.7% for those treated with linear plates. Surgical time in single fractures between Linear System versus 3D System was similar (p=0.7322) as was surgical time (p=0.4574). The amount of bleeding in single fractures between Linear vs. 3D System was also similar (p=0.285), as was that of double fractures (p=0.6642). Conclusions: These data suggest that the procedure employed, and the material used is at the discretion of the surgeon.